Maximizing Value - A Look Back at FGV Holdings Berhad - Muhd Adib Afza Mohd Norkamar; Abdul Razak Abdul Hadi (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2023)
This paper explores a number of relevant capital structure theories that may help explain the real market occurrence. The debt-equity ratio is commonly utilized as a variable of interest by many to evaluate the viability of company’s capital structure. Based on Modigliani-Miller Trade-Off theory (1958), their major goal is to examine how firm-specific capital structure determinants may impact the company's capital structure choice. It is essential to comprehend how firm-specific factors could exert a direct impact on a company's share price in both the short and long run. In the case of FGV Holdings Berhad, its capital structure composition has shifted from equity-weighted to debt due to FGV's improved cash flow situations, allowing them to secure wider options of financing from the capital markets. As a result, the company's total debt to total assets ratio has risen dramatically to 76.4 percent. However, it is vital to note that FGV's debt interest payments are not adequately supported by profits before interest and tax (EBIT). Debt financing invariably requires interest payments, regardless of whether it is provided through the bond or banking markets. The net result could jeopardize the company’s value through declining share price. The Trade-off theory is seen ideal in explaining the financial conditions in FGV. It is important to balance out the benefits of debt against the costs of debt at all times. Overall, FGV's top management should consider conducting a thorough review on its entire capital structure since the debt levels have climbed dramatically since 2014, along with a declining cash level in mid-2014.